The economics of coercion and conflict - Harrison, Mark 1949- (The tricontinental series on global economic issues, 2251-2845, 2015)
The papers brought together in this volume represent a decade of advances in the historical political economy of defence, dictatorship, and warfare. They address defining events and institutions of the world in the twentieth century: economic consequences of repression and violence, the outcomes of two world wars, and the rise and fall of communism. They cross traditional disciplinary boundaries, combining a broad sweep with close attention to measurement and narrative detail; offering insights into these issues from economics, history, political science, and statistics; and demonstrating in action the value of a multi-disciplinary approach. The author was one of the first economists to leverage the opening of former Soviet archives. He has led international projects that reinvented the quantitative economics of the two world wars and contributed significantly to historical Soviet studies. In 2012, he shared with Andrei Markevich the Russian National Prize for Applied Economics, which was awarded in recognition of their research